PENGARUH VARIASI FILLER PADA CAMPURAN SAMI-R DENGAN MENGGUNAKAN 20% KARET TERHADAP KARAKTERISTIK MARSHALL - Ihram Fajar; Edward Ngii; La Ode Muhammad Nurrakhmad Arsyad (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2017)
Abstract SAMI (Stress Absorbing Membrane Interlayer) is an application maintenance or maintenance on existing pavement used to prevent cracks from the bottom layer to get to the new surface layer (overlay). SAMI is an intermediate layer at the interface between layers of asphalt that absorbs stress to reduce the crack (stress-relieving interlayer) in the overlay layer.The purpose of this research is to know the Marshall characteristics of mixed SAMI-R mixture using rubber of 20% in each variation. (Variation I Sand 90% and Cement 10%, Variation II Sand 80% and Cement 20%, and Variation III Sand 70% and Cement 30%).These results indicate that the stability of the three design variations meet the specifications Latasir with values obtained over 200 kg. Values for the flow of the three design variations none meet specifications with a value between 2-3 mm. The results obtained for the value of Marshall Quotient (MQ) in variations II and III levels for different types of asphalt meet the specifications Latasir. For percentage values Void In The Mineral Aggregate (VMA) for the third design variation values obtained percentages above 20%, so that the third draft of these variations can meet the specifications. Void values obtaine Filled With Asphalt (VFWA) on draft variation I with asphalt content of 10%, 11%,  and 12%, by value VFWA percentage above 75%. While the value of Void In The Mix (VIM) is obtained on draft variation I in the asphalt content of 10%, 11%,  and 12%, with the percentage of 4.14% and 4.74%, so it makes the specification Latasir with VIM percentage value between 3-6&%.